Privatization of migration control : power without accountability? - Sarat, Austin (Studies in law, politics, and society ;, 2021)
This special issue is part one of a two-part edited collection on the privatisation of migration. The central thrust of the special issue is a critical analysis of modern day manifestations of private participation in immigration control such as through companies which run detention and deportation programmes and individual landlords, medical professionals and employers who become part of immigration enforcement. In the chapters the authors examine the consequences of private participation in terms of legal rights and liabilities.